Math CentralQuandaries & Queries


Question from Kathy, a parent:

My daughter and I are having trouble solving this equation:

-x²+ (yz - 3)²

if x= -4,y=2 and z=0
We are having difficulty with the -x² part of the equation. Thanks


The convention in evaluating a mathematical expression is to evaluate exponents (powers) before multiplication or addition. Thus for -x2 you first evaluate x2 and then multiply by -1. Hence with x = -4, x2 = (-4)2 = 16 and therefore -x2 = -16.

I hope this helps,

About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS